Analysis of kinematic variables in soccer kicking technique from biomechanical efficiency criteria - Camacaro, Marelvy; Colina, Alberto; Zissu , Mihai (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The present investigation was carried out with the objective of analyzing the kinematic variables that are manifested in the kicking technique in soccer based on biomechanical efficiency criteria. It was a descriptive level investigation, with a field design, based on a case study with a 15-year-old athlete. The three-dimensional (3D) videographic method was used with the approaches: quantitative (“Human v 5.0” program) and qualitative (Likert scale). Kinematic variables were quantified by pre and posttest. Efficiency criteria were established to optimize biomechanical variables in the phases: Preparatory and Kicking. Thus, the adolescent's training was oriented according to the strengths and weaknesses identified from the biomechanical perspective, which allowed optimizing the technique of the dominant and non-dominant lower limbs. Among other results, the increase in synchronization and consequent improvement in the temporal pattern of movement stood out, which facilitated the coordination of partial impulse, and therefore the transfer of energy from the body to the ball, positively influencing the resulting speed, trajectory and precision of the ball which increased the frequency of the goal, a fact that affected the performance and profile of the young woman, standing out in the lateral position with an efficient handling of the ball by both profile.